Folded paper German stars : creative paper crafting ideas inspired by Friedrich Fröbel - Täubner, Armin (Stackpole Books, 2012)
"Paper folding crafts are fun for all ages! You'll be amazed at what you can create with pretty paper and a few strategic folds. Colorful Fröbel stars can be used as ornaments, table decorations, candle holders, and more, and a variety of other shapes make festive gift toppers, toys, mobiles, and garlands. Step-by-step, illustrated instructions show you how to make more than 30 different designs. Projects range from simple to complex, so there is something for everyone. Paper crafts build creativity, basic mathematical principles, and fine motor skills. Precise drawings and detailed instructions make these projects easy to do, even for children"--Amazon.com.